The Embodied Work of Multimodality in Teaching English Pronunciation of Consonants Unavailable in Indonesian Language - Kusrin Kusrin; Evi Karlina Ambarwati; Indah Purnama Dewi (Journal of English Language Studies, 2023)
Multimodal learning environment has been facilitating teachers to present information-rich in technical words and symbols in picture-print as well as picture-spoken words materials to non-native learners. Indeed, many laboratory and experiment conditions have investigated the positive effect of multimodality to pronunciation learning but little is known about applying it in teaching English consonants that are unavailable in Indonesian language.  This naturalistic case study explored the experience of five pre-service English teachers when learning English consonants unavailable in Indonesian language, i.e., /ð/; /Ɵ/; /ʃ/; and /ʒ/. The data were collected by means of students’ reflective journals and interview. Findings suggest that the participants utilized the picture-word materials to understand the consonants’ phonetic symbols. The picture-spoken words materials facilitate students’ sound production practices. Last, the students’ motivation to acquire intelligibility and comprehensibility is shaped by their identity as pre-service English teachers believe that their correct pronunciation reflects their professional competence and improve their confidence.